Welcome Mr. Maura: Conservatism and Free Trade on the Eve of an Argentinian Fascism - Faes Díaz, Enrique (Hispania Nova, 2023)
This article studies the mentality of Antonio Maura Gamazo as Spanish businessman who traveled to Argentina in 1913, connecting Spanish emigrants with local elites. It explores, through his figure, business adaptation strategies in the post-war context and definition of new links. Areas where conservative mentalities converge are also studied, since the period was key to the radicalization of right-wing political options.
Keywords: conservatism; businessmen; transnational perspective; biography; international trade